The NLR-Annotator Tool Enables Annotation of the Intracellular Immune Receptor Repertoire. Issue 2 (17th March 2020) - Steuernagel, Burkhard; Witek, Kamil; Krattinger, Simon G.; Ramirez-Gonzalez, Ricardo H.; Schoonbeek, Henk-jan; Yu, Guotai; Baggs, Erin; Witek, Agnieszka I.; Yadav, Inderjit; Krasileva, Ksenia V.; Jones, Jonathan D.G.; Uauy, Cristobal; et al.
Abstract : The wheat intracellular immune receptor repertoire can be explored with the NLR-Annotator tool. Abstract: Disease resistance genes encoding nucleotide-binding and leucine-rich repeat (NLR) intracellular immune receptor proteins detect pathogens by the presence of pathogen effectors. Plant genomes typically contain hundreds of NLR-encoding genes. The availability of the hexaploid wheat ( Triticum aestivum ) cultivar Chinese Spring reference genome allows a detailed study of its NLR complement. However, low NLR expression and high intrafamily sequence homology hinder their accurate annotation. Here, we developed NLR-Annotator, a software tool for in silico NLR identification independent of transcript support. Although developed for wheat, we demonstrate the universal applicability of NLR-Annotator across diverse plant taxa. We applied our tool to wheat and combined it with a transcript-validated subset of genes from the reference gene annotation to characterize the structure, phylogeny, and expression profile of the NLR gene family. We detected 3, 400 full-length NLR loci, of which 1, 560 were confirmed as expressed genes with intact open reading frames. NLRs with integrated domains mostly group in specific subclades. Members of another subclade predominantly locate in close physical proximity to NLRs carrying integrated domains, suggesting a paired helper function. Most NLRs (88%) display low basal expression (in the lower 10 percentile of transcripts). In young leaves subjected to biotic stress, we found up-regulation of 266 of the NLRs . To illustrate the utility of our tool for the positional cloning of resistance genes, we estimated the number of NLR genes within the intervals of mapped rust resistance genes. Our study will support the identification of functional resistance genes in wheat to accelerate the breeding and engineering of disease-resistant varieties.